Development of an electro-adhesive micro pillar array via EHD patterning. (5th February 2019) - Itoh, K; Ishida, M; Kakinuma, Y; Anzai, H; Sakirai, K
Abstract: Electro-adhesive gel (EAG) is a functional material that exhibits an electrically controllable adhesive force. The adhesive characteristic of EAG highlights potential applications in fixing or handling devices. However, the EAG adhesive area under an applied electric field is often irregular due to particle distribution at the surface, which therefore leads to a large variance in the adhesive force of each sample. This paper proposes the development of an electro-adhesive pillar array (EAPA) to stabilize and improve the performance of the electro-adhesive force regardless of the sample. Electro-hydrodynamic patterning, which is a novel technique to fabricate micro-/nanostructures in a polymer film, is introduced to fabricate the pillar array. The proposed fabrication method and process are first discussed, and a preferred template design is verified. Furthermore, the fabrication process is improved with a UV-curing polymer and surface treatment of the template. The experimental results show that the improved EAPA successfully achieves a higher fixing force with a uniform adhesive area. The proposed EAPA clearly shows a better electro-adhesion performance than conventional EAG.